[Zn(TAC)]Cl complex potential as corrosion inhibitors: synthesization and characterization / Siti Aisyah Musa and Nur Nadia Dzulkifli - Musa, Siti Aisyah; Dzulkifli, Nur Nadia (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Corrosion of metal is a severe issue in any industry which is considered to involve many costs. The use of acid solution during cleaning to get rid of rust in industries may contribute to metal corrosion. Since corrosion impact is causing worries, especially in many industries, the application of a corrosion inhibitor is required to reduce the rapid deterioration reaction of a metal surface that is exposed to corrosion ‘boosters’ like oxygen gas and water. A corrosion inhibitor, which is [Zn(TAC)]Cl, was produced from the reaction between thiacetazone (TAC) with ZnCl 2 in an acetonitrile solvent with ratio 1:1 (ligand:metal). The elemental analysis (C, H, N, and S), FT-IR, UV-Visible, melting point, gravimetric analysis, and molar conductivity were used to characterize the synthesized complex. Based on infrared spectra and electronic transitions, the shifting of a complex from the ligand indicates that the ligand is coordinated to the metal ion through carbonyl O, azomethine N, and thiolate S; thus, producing a tridentate complex. Melting point for the complex was higher than ligand. [Zn(TAC)]Cl was gained after being confirmed by 1:1 electrolyte behavior and elemental analysis calculations. A metal oxide, ZnO, was formed with the calculated percentage of Zn(II) ion, 13.66 % after combustion through the gravimetric analysis. [Zn(TAC)]Cl portrayed better inhibitory action against corrosion of mild steel as compared to the ligand in both acidic media, H 2 SO 4 and HCl. A higher concentration of inhibitor gave a higher percentage of corrosion inhibition efficiency.